2010
DOI: 10.1172/jci42680
|View full text |Cite
|
Sign up to set email alerts
|

Selective ablation of basophils in mice reveals their nonredundant role in acquired immunity against ticks

Abstract: Ticks are ectoparasitic arthropods that can transmit a variety of microorganisms to humans and animals during blood feeding, causing serious infectious disorders, including Lyme disease. Acaricides are pharmacologic agents that kill ticks. The emergence of acaricide-resistant ticks calls for alternative control strategies for ticks and tick-borne diseases. Many animals develop resistance to ticks after repeated infestations, but the nature of this acquired anti-tick immunity remains poorly understood. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
359
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 275 publications
(377 citation statements)
references
References 53 publications
(101 reference statements)
17
359
0
1
Order By: Relevance
“…In the past few years nonredundant protective functions of basophils have been observed during secondary infections with helminths and ticks (13,14,17). However, the underlying mechanisms remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years nonredundant protective functions of basophils have been observed during secondary infections with helminths and ticks (13,14,17). However, the underlying mechanisms remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past years several genetic mouse models have been used to elucidate basophil functions in vivo. It has been shown that basophils cooperate with dendritic cells to initiate Th2 responses, promote alternative activation of macrophages, and contribute to acquired resistance against parasites (12)(13)(14)(15)(16). We and others have shown that basophils contribute to protective immune responses against secondary infection by Nb and ticks (13,14,17).…”
mentioning
confidence: 84%
“…However, in some inflammatory conditions, basophils are recruited to the skin (15). Although they share morphological and functional similarities with mast cells, basophils have unique functions; for example, in addition to producing IL-4 and IL-13 (16)(17)(18), they play important roles in acquired immunity against helminths and ticks and in IgGdependent anaphylactic reactions (19)(20)(21). Thus, certain allergic events, in particular Th2-type immune responses, are likely involved in the pathogenesis of prurigo, although the details of the underlying mechanism have not been clearly defined.…”
mentioning
confidence: 99%
“…A knock-in system of the diphtheria toxin receptor (DTR) gene into the Mcpt8 locus is another promising tool that was recently established (15). However, there is still a need for tools to precisely distinguish and investigate MC and basophil functions in the same experimental system.…”
mentioning
confidence: 99%